Revision of the Rhinophoridae (Diptera: Calyptratae) of Japan - Kato, Daichi; Tachi, Takuji (Zootaxa, 2016)
The Japanese species of the family Rhinophoridae are revised. Melanophora roralis (Linnaeus) is newly recorded from Japan and is hypothesized as having been introduced to the country; one species, Acompomintho itoshimensis sp. nov., is described as new. Images of the habitus, wing and male terminalia are provided for all four Japanese species, together with an identification key and a map showing their distribution.